Association between Promotor hypomethylation of TFF1 and Crohn’s Disease - Hemmati, Sara; Sanati, Golshid; Sadeghi, Mohammad Amin; Ebrahimi Daryani, Naser; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Epigenetic modifications exhibit promising evidence in etiology and prognosis of important diseases such as inflammatory bowel diseases (IBD). In addition to complex factors involved in IBD, a trend toward better prognosis have been reported in older ages of disease onset. Gastrointestinal mucous layer is one of the important components which is disturbed in the disease course. Integrity of this layer is maintained with an anti-inflammatory factor called trefoil factors (TFF). We investigated the methylation status of TFF1 gene in IBD patients alongside with correlation of its alteration level with age of disease onset. Methods: We analyzed the promoter methylation status of TFF1 gene, using the real-time quantitative multiplex methylation specific PCR (QM-MSP). DNA was extracted from colorectal biopsies of 15 Crohn disease cases and 15 healthy controls. Correlation analysis was performed between unmethylated DNA level and age through Pearson correlation coefficient (PPC) test and simple linear regression models. Results:… Our data didn’t provide significant positive correlation of age and TFF1 hypomethylation in Crohn patients (r = .518, p = .058). Conclusions: In conclusion, our case-control study didn’t show significant alteration in TFF1 methylation status in CD patients. (www.actabiomedica.it)